Effectiveness of Tea Leaf (Camellia sinensis) Liquid Smoke as an Antiseptic - Rohmah, Fitriani Nurhidayati; Alamsyah, Muhamad Thamrin; Nurjana, Siti; Fadhila, Feldha; Mayuri, Nindya Sekar; Rumidatul, Alfi (3BIO: Journal of Biological Science, Technology and Management, 2024)
Microbes are often the cause of infectious diseases; one method of prevention is to use antiseptics. Excessive use of antisep- tics can cause mild to severe side effects, so an alternative antiseptic is needed. Liquid smoke is an alternative raw material to produce antiseptics because its main component can be used as an inhibitor of microbial growth. This study aims to determine the effectiveness of tea-leaf liquid smoke as an antiseptic against microbial growth in vivo and in vitro. The method for producing liquid smoke via pyrolysis involves distilling grade 3 liquid smoke to generate grade 1 and grade 2 liquid smoke. The in vitro test uses a microbial growth inhibition test with grade 1 and 2 liquid smoke concentrations of 35%, 50%, and 75%. The microbes used were Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Candida albicans ATCC 10231, and Aspergillus flavus ATCC 9643. The in vivo test uses the swab test method on the palm of the hand. The results of the invitro test showed that the largest inhibition zone of tea leaf liquid smoke was obtained using grade 2 liquid smoke with a concentration of 75%.The results of the in vivo test showed that the effectiveness of tea leaf liquid smoke was 80% against bacteria and 85% against fungi. Based onthe results of the study, it can be concluded that tea leaf liquid smoke (Camellia sinensis) has potential as an antiseptic.